Assessing Professional Fulfillment and Burnout Among CEOs and Other Healthcare Administrative Leaders in the United States. Issue 5 (17th September 2022) - Shanafelt, Tait; Trockel, Mickey; Wang, Hanhan; Mayer, Thom; Athey, Leslie
Abstract : Goal: The objective of this study was to evaluate the prevalence of burnout and professional fulfillment among healthcare administrative leaders and examine the association between burnout and professional fulfillment and personal and professional characteristics. Methods: Between June 7 and June 30, 2021, we performed a national survey of CEOs and other senior operational leaders to evaluate their personal work experience. Burnout and professional fulfillment—as well as a sleep-related impairment and self-valuation—were assessed using standardized instruments. Principle Findings: Of the 5, 994 members of the American College of Healthcare Executives who were sent an invitation to participate, 1, 269 (21.2%), including 279 CEOs, submitted usable responses. The mean overall burnout score was 2.71 (range: 0–10), and 33% of participants had burnout scores that fell in the high range (unfavorable). Mean professional fulfillment score was 7.29 (range: 0–10), with 56.6% scoring in the high range (favorable). Burnout and professional fulfillment scores varied by role. On multivariable analysis, sleep-related impairment (OR for each 1-point increase = 1.29, 95% CI [1.19–1.41]; p < .001) and self-valuation (OR for each 1-point increase = 0.63, 95% CI [0.57–0.68]; p < .001) were independently associated with burnout after adjusting for all other variables. Applications to Practice: Results of this study suggest that healthcare leaders had lower burnout and professional fulfillment scores than clinicians. Nonetheless, one third of healthcare leaders had burnout scores that fell in the high range. At the individual level, improved sleep health and self-valuation appear to reduce risk of burnout and promote professional fulfillment.